PUBLIC INTERACTIVE ELECTRONIC TEXTBOOKS ON MATHEMATICAL DISCIPLINES. NEW CDF-TECHNOLOGY OF CREATION - Evgenii M. Vorobev; Valerii A. Nikishkin (Статистика и экономика, 2016)
We discuss a new information technology for designing interactive e-tutorials in mathematics. We also present an example of such a tutorial. The technology, called “Computable Document Format” (CDF), proposed by Wolfram Research, Inc. - the developer of the well known mathematical program system “Mathematica”. The interactivity of the tutorials means that the latter contain the executable mathematical objects such as formulae, graphs of functions, etc. together with the definitions, theorems, proofs and so on. The user makes his choice of presupposed variants of mathematical objects for calculation at the moment of reading the tutorial.